A systematic mapping review of persuasive speaking strategies among entrepreneurs in digital business environment - Nurjanah Mahat,; Azlina Abdul Aziz,; Hanita Hanim Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Persuasive strategies used in business presentations by many entrepreneurs to market their products to potential customers are important strategy in gaining customers’ trust. While various means of social media used to reach to their customer, literature shows that little attention has been given to the study of persuasive strategies in English discourse for the entrepreneurs using TikTok. Previous research had discussed marketing strategies rather than focusing on the arts of delivery, semantics, and persuasive elements in online business presentation. Thus, the aim of this study is to collect and extract information from the literature in search for the research gap, and analyse the most significant studies in the teaching of persuasive strategies on social media especially TikTok. The searching process will focus on papers published in journals from 2019 until 2023 using a systematic mapping review (SMR). A total of 239 relevant research papers from Scopus, Web of Science, Google Scholars online databases were retrieved. Nine final papers were selected in the study. Results from the review showed that the predefined requirement criteria which are the keywords such as persuasive strategies, entrepreneurs and social media were not all discussed as a whole idea and therefore they were not all satisfied in literature. There are limited studies on the persuasive strategies using English discourse in TikTok. Thus, a conceptual framework of measurement for teaching persuasive strategies using English discourse in TikTok by entrepreneurs should be developed to provide a comprehensive competency measurement and determining relevant persuasive strategies using English discourse in social media among entrepreneurs.